Critical Synthesis Package: Hatfield Global Measure of Equity Scale - Brenessa Lindeman (Association of American Medical Colleges, 2014)
Abstract This Critical Synthesis Package contains: (1) a Critical Analysis of the psychometric properties and the application to health science education of the Hatfield Global Measure of Equity Scale, and (2) a copy of the Hatfield Global Measure of Equity Scale instrument with scoring instructions developed by Brenessa Lindeman, MD. The Hatfield Global Measure of Equity Scale is a one-item instrument that may be administered via survey or interview. Respondents are asked to consider both their own investments in and outcomes from a designated relationship compared to that of their relationship partner, across seven response options presented along a Likert-type scale ranging from −3 (indicates partner benefitted more) to +3 (indicates respondent is benefitted more). A response of 0 indicates the partners benefit equally from the relationship. Presence of equity in a relationship, as measured by the Hatfield Scale, has been demonstrated to correlate with other measures of life and relationship satisfaction. This correlation has remained durable across multiple types of relationships (intimate, collegial, organizational) and across various populations (married and dating couples, teacher-student, therapist-patient, resident physician-supervisor). Some debate exists as to whether this global measure is superior to more detailed assessments of equity in relationships, as mixed results have emerged when these scales are correlated, but this instrument continues to serve as the gold standard in assessment of individuals' general sense of the reciprocity of their relationships.